Practice recommendations and referrals, perceptions of efficacy and risk, and self-rated knowledge regarding complementary medicine: a survey of Australian psychologists - Carrie Thomson-Casey; Erica McIntyre; Kris Rogers; Jon Adams (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Many people with mental health problems use a range of complementary medicine (CM), including over the counter products, practices, and utilise the services of CM practitioners. Psychologists are likely to consult with clients using CM, in some form, as part of their broader mental health care. The aim of this research was to determine the number of types of CM products, practices, and practitioners are recommended and/or referred by Australian psychologists as part of their clinical practice, as well as explore the relationship between psychologists’ perspectives on the risk and relevance of engaging with CM in psychology. Methods Survey data was collected from psychologists in clinical practice who self-selected to participate in the study via an online 79-item questionnaire exploring core aspects of CM engagement in psychology clinical practice. Results Amongst the 201 psychologists, 5% reported not recommending any type of CM, with 63% recommending four or more types of CM. Further, 25% had not referred to a CM practitioner, while 33% had referred to four or more types of CM practitioner. Psychologists are recommending and referring to CM even when they perceive their knowledge of CM to be poor, and that engaging with CM was a risk. Conclusion This study provides insights into psychologist perceptions of CM within psychology practice and how these perceptions are associated with rates of recommending and referring to CM as part of their clinical practice. These findings may inform the development of CM relevant education and guidelines for psychologists.